New trends in sugarcane fertilization: Implications for NH3 volatilization, N2O emissions and crop yields - Oliveira, Bruna G.; Lourenço, Késia S.; Carvalho, João Luis N.; Gonzaga, Leandro C. [UNESP]; Teixeira, Maria Carolina; Tamara, Ana Flávia; Soares, Johnny R.; Cantarella, Heitor (Elsevier, 2023)
Recycling nutrients helps to reduce the environmental impact of agriculture and contributes to alleviating the effects of global climate change. A recent trend in sugarcane cultivation is the application of concentrated vinasse (CV) combined with fertilizers into an organo-mineral formulation to improve logistics, reduce costs and foster the circular economy. However, the implications of the application of such organo-mineral formulation in sugarcane fields are unclear. In this study, we evaluated the effects of the organo-mineral formulation containing granular urea (UR), and a nitrification inhibitor (NI) on crop yields, NH3 volatilization, and N2O emissions. Field experiments were conducted during two fertilization seasons, dry and wet, and the treatments were: control; UR; UR + NI; CV; CV + UR; and CV + UR + NI. CV was applied at 7 m3 ha−1. The treatments (except control and CV) were balanced to receive the same amount of N and K. Compared with UR, the organo-mineral formulation of CV + UR decreased NH3 volatilization losses from 7% to 4% in the dry season and from 3.5% to 0.5% in the wet season. Conversely, compared with UR, N2O emissions increased significantly (p ≤ 0.05) in CV + UR in the wet season from 1% to 2% of applied N. In the dry season, no differences were observed. The addition of NI was effective in mitigating N2O emissions in both seasons. Emission reductions ranged from 43 to 48% in the dry season and from 71 to 84%, in the wet season. Fertilization with UR or the organo-mineral formulation influenced sugarcane yield only in the dry season, with the highest yield in CV + UR. NI did not affect crop yield. In general, emission intensities (kg CO2eq Mg−1 of stalk) were highest in CV + UR. We conclude that the organo-mineral formulation reduced NH3 losses and increased N2O emissions compared with regular solid fertilizer and that NI was effective for mitigating N2O emissions.
Keywords: Concentrated vinasse; GHG emissions; Organo-mineral fertilizer; Urea